1993
DOI: 10.1002/ffj.2730080106
|View full text |Cite
|
Sign up to set email alerts
|

On the genuineness of citrus essential oils. Part XLI. Italian bitter orange essential oil: Composition and detection of contamination and additions of oils and terpenes of sweet orange and of lemon

Abstract: The composition of the volatile fraction of Italian bitter orange essential oil, camed out by LC, HRGC and GC-MS, is reported: 60 components have been identified. The results obtained are compared with those in the literature for Italian and Spanish bitter orange oils.Two methods are suggested which allows the detection of contamination or possible additions of terpenes and oils of sweet orange and of lemon to genuine bitter orange oil. One is based upon the content of 6-3-carene and the value of the ratios 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 5 publications
0
14
2
Order By: Relevance
“…Several investigations have confirmed the limonene importance in Citrus juice [36, 37]. Moufida and Marzouk [30] showed that limonene was the major volatile component of four Citrus species representing 63% in blood orange and 90% in sour orange.…”
Section: Resultsmentioning
confidence: 96%
“…Several investigations have confirmed the limonene importance in Citrus juice [36, 37]. Moufida and Marzouk [30] showed that limonene was the major volatile component of four Citrus species representing 63% in blood orange and 90% in sour orange.…”
Section: Resultsmentioning
confidence: 96%
“…Bitter orange peel oils from Italy consist mainly for limonene (94.3%), myrcene (1.88%), linalool (0.78%) and ␣-pinene (0.4%) as reported by Caccioni et al, (1998). Additionally, Dugo et al, (1993) noted that bitter orange essential oils were dominated by monoterpene hydrocarbons (97%) whereas alcohols, aldehydes and esters represent the oxygenated compounds with the lowest percentages, varying from 1.80 to 2.20%. These qualitative and quantitative differences in oil compositions depended on various factors such as genotype, season, maturational stage and pedoclimatic factors .…”
Section: Tablementioning
confidence: 82%
“…Linalyl acetate is the main oxygenated compound and it represents the major part of the esters. Linalool is the main alcohol and octanal and decanal the main carbonyl compounds …”
Section: Introductionmentioning
confidence: 99%